Disentangling the Influence of Environment, Host Specificity and Thallus Differentiation on Bacterial Communities in Siphonous Green Seaweeds - Morrissey, Kathryn Lee; Çavaş, Levent; Willems, Anne; De Clerck, Olivier (Frontiers in Microbiology, 2019)
Siphonous green seaweeds, such as Caulerpa, are among the most morphologically complex algae with differentiated algal structures (morphological niches). Caulerpa is also host to a rich diversity of bacterial endo- and epibionts. The degree of which these bacterial communities are species-, or even niche-specific remain largely unknown. To address this, we investigated the diversity of bacteria associated to different morphological niches of both native and invasive species of Caulerpa from different geographic locations along the Turkish coastline of the Aegean sea. Associated bacteria were identified using the 16S rDNA marker gene for three morphological niches, such as the endobiome, epibiome and rhizobiome. Bacterial community structure was explored and deterministic factors behind bacterial variation were investigated. Of the total variation, only 21.5% could be explained. Pronounced differences in bacterial community composition were observed and variation was partly explained by a combination of host phylogeny, biogeography and nutrient levels. The majority of the explained bacterial variation within the algal holobiont was attributed to the micro-environments established by distinct morphological niches. This study further supports the notion that the bacterial assembly is largely stochastic in nature and bacterial community structure is most likely linked to functional genes rather than taxonomy.